REAL ESTATE MARKET REGULATION AND PROPERTY VALUES IN LAGOS STATE, NIGERIA - Olawande, Oni Ayotunde; Adedapo, Oluwatayo; Daniel O., Durodola (European Scientific Journal, ESJ, 2012)
Increasing demand for commercial and residential properties has caused increase in rental values while the Government has intervened through enactment of the Rent Control and Recovery of Residential Premises (RCRRP) Edict (1997). This paper examined the effects of the law on residential property values in the study area. In doing so, a process of inference to evaluate the law was adopted, in addition to multiple-samples comparison and analysis of variance of the controlled and open market rents. Furthermore, hypothetical design of three-bedroom flats was used to illustrate the valuation of residential properties under the RCRRP Edict. The study found that with alpha level set at 0.05, rent control has no statistically significant effect on rental values, P-value=0.0009. It recommended that Government should not regulate the real estate market but provide enabling environment for investors to provide low cost housing units that would in the long run reduce rental values.